Configuration of the Operation Modes for a Scintillating Fiber Sub-Detector in LHCb Experiment - Tomás Sierra-Polanco; Diego Milanés; Carlos E. Vera (Ciencia e Ingeniería Neogranadina)
In order to develop new techniques for the knowledge of the universe some experiments in elementary particles and high energy physics are proposed, where progress on detector and data acquisition techniques is fundamental. This project presents some improvements for the LHCb upgrade that will be performed in the period between 2018 and 2019 during the Long Shutdown 2 of the CERN experiments in order to configure, improve and re-structure the data acquisition practices. It will emphasize the Scintillating Fibers detector (SciFi), one of LHCb's future sub-detectors in charge of the trace pattern recognition based on the hits occurred on this sub-detector and the recording of significant events in the data transmission. Due to the proposed changes of the LHCb upgrade, regarding the increase of the luminosity and the collision center-of-mass energy, it is essential to reconsider the digital processes in the data acquisition and their respective processing among the transmission channels, due to the high velocities at which they occur. Therefore, the operation mode configurations in the acquisition digital boards were the aim of this work. And as such, the current condition of the detector and its acquisition techniques and protocols are documented corresponding to their modification. This paper shows a step-by-step presentation of the modifications applied to the codes to move from a Standard Mode to a Wide Bus Mode, increasing the data rate by means of the quantity reduction of the control bits to enlarge the amount of analyzable information among the events.